The Challenges of Struggling Writers: Strategies That Can Help - Michael Dunn (MDPI AG, 2021)
Writing is a necessary skill in our technological world. Many people have a mobile device that they use for e-mailing, social media, as an alarm clock to start the day, reading the news, searching for information, ordering food, managing transportation (e.g., monitoring traffic, accessing public transit), or for relaxing pursuits, such as watching a movie or listening to music. While these tasks are natural and almost effortless for numerous people, many students struggle with composing longer prose, especially for academic tasks. The 2021 U.S. National Assessment of Educational Progress for Writing, for example, indicates that as many as 75% of students cannot write at a basic level. In this article, the author discusses recent examples from the professional literature about why writing can be a challenge for students, what is involved in writing assessment, how we can help students improve their writing skills, and how we can promote technology as part of the instruction and learning processes.